FINTECH LITERACY, HEDONIC LIFESTYLE, AND PAYLATER USE: GENDER AS A MODERATOR - Deasy Tantriana; Sofia Ranti Rahmah Riska Hidayat (CURVE: Journal of Economic, Business and Accounting, 2026)
This study examines the effects of fintech literacy and hedonic lifestyle on PayLater use and tests gender as a moderator among Generation Z in Surabaya. A quantitative survey involved 196 PayLater users aged 18–28 selected through purposive sampling, equally divided between 98 men and 98 women. Data were analyzed using PLS-SEM and multi-group analysis in SmartPLS 4. Fintech literacy positively affected PayLater use (β = 0.560; p < 0.001), as did hedonic lifestyle (β = 0.350; p < 0.001), while the model explained 74.5% of the variance. Fintech literacy had a stronger effect among women (β = 0.771) than men (β = 0.494), with a significant group difference (p = 0.004). Conversely, hedonic lifestyle was significant among men (β = 0.403; p < 0.001) but not women (β = 0.128; p = 0.106), and the group difference was significant (p = 0.013). Fintech literacy may therefore facilitate PayLater use rather than automatically restrain it. Digital financial education should integrate operational competence, responsible credit management, and gender-sensitive safeguards.